2021
DOI: 10.1111/jocs.16106
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of SARS‐CoV‐2 on patients undergoing cardiac surgery

Abstract: Objective: To analyze Italian Cardiac Surgery experience during the pandemic of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) identifying risk factors for overall mortality according to coronavirus disease 2019 (COVID-19) status.Methods: From February 20 to May 31, 2020, 1354 consecutive adult patients underwent cardiac surgery at 22 Italian Centers; 589 (43.5%), patients came from the red zone. Based on COVID-19 status, 1306 (96.5%) were negative to SARS-CoV-2 (COVID-N), and 48 (3.5%) were posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…In the event teams pursue cardiac intervention, necessary provisions should be made for appropriate postoperative care given the recognition that patients are likely to incur more medical complications and experience longer intensive care unit length of stay. 26,38,39 EMERGENT INTERVENTION. If the procedure is deemed emergent or if procedural indication becomes emergent during the period of procedural delay, it is advisable to proceed immediately with the intervention, assuming teams observe the necessary precautions to avoid disease transmission, which are outlined in full in prior guidelines.…”
Section: Individualized Cardiac Procedures Triage and Timingmentioning
confidence: 99%
“…In the event teams pursue cardiac intervention, necessary provisions should be made for appropriate postoperative care given the recognition that patients are likely to incur more medical complications and experience longer intensive care unit length of stay. 26,38,39 EMERGENT INTERVENTION. If the procedure is deemed emergent or if procedural indication becomes emergent during the period of procedural delay, it is advisable to proceed immediately with the intervention, assuming teams observe the necessary precautions to avoid disease transmission, which are outlined in full in prior guidelines.…”
Section: Individualized Cardiac Procedures Triage and Timingmentioning
confidence: 99%
“…However, emergency surgery and a positive SARS2 PCR test only marginally affected adverse outcomes. One study found that age and being SARS2 PCR positive had a significant prognostic value in cardiac surgery [ 13 ]. However, in this study, most patients were symptomatic, and a history of heart failure was more common among PCR-positive patients.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, concerning the subjects belonging to the COVID-19 era group (for whom COVID-19 screening test was available), 2 patients tested positive for COVID-19 on hospital admission: one survived and the other didn’t. Even if recent studies have described a significantly higher mortality for COVID-19-positive patients undergoing cardiac surgery, such small numbers make any further conclusion unfeasible [ 30 ]. Moreover, only one patient got COVID-19 infection during hospital stay, that later represented the cause of death.…”
Section: Discussionmentioning
confidence: 99%